2022
DOI: 10.1175/jpo-d-21-0116.1
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater Input and Vertical Mixing in the Canada Basin’s Seasonal Halocline: 1975 versus 2006–12

Abstract: The Arctic seasonal halocline impacts the exchange of heat, energy, and nutrients between the surface and the deeper ocean, and it is changing in response to Arctic sea ice melt over the past several decades. Here, we assess seasonal halocline formation in 1975 and 2006-2012 by comparing daily, May to September, salinity profiles collected in the Canada Basin under sea ice. We evaluate differences between the two time periods using a one-dimensional (1D) bulk model to quantify differences in freshwater input a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
1
0
0
Order By: Relevance
“…The data in this study are identical to those employed by Rosenblum et al. (2021), who showed that June‐September surface changes between the ITP and AIDJEX datasets are consistent with 30‐year mixed‐layer trends reported by Peralta‐Ferriz and Woodgate (2015) using data mainly associated with low sea ice concentration in the same region. They used only quality‐controlled data (level 3) in the ITP archive, screened profiles to select those that include samples shallower than 10 m depth (as in Jackson et al., 2010), and that were collected during the period May 1 ‐ December 31, which is common to both datasets.…”
Section: Methodssupporting
confidence: 86%
“…The data in this study are identical to those employed by Rosenblum et al. (2021), who showed that June‐September surface changes between the ITP and AIDJEX datasets are consistent with 30‐year mixed‐layer trends reported by Peralta‐Ferriz and Woodgate (2015) using data mainly associated with low sea ice concentration in the same region. They used only quality‐controlled data (level 3) in the ITP archive, screened profiles to select those that include samples shallower than 10 m depth (as in Jackson et al., 2010), and that were collected during the period May 1 ‐ December 31, which is common to both datasets.…”
Section: Methodssupporting
confidence: 86%